Basis of single-seed formation in chestnut: cytomorphological observations reveal ovule developmental patterns of Castanea henryi - Qi Qiu; Xiaoming Tian; Guolong Wu; Juntao Wu; Deyi Yuan; Xiaoming Fan (PeerJ)
Background Many plants, including those commonly found in the Fagaceae family, produce more flowers and ovules than mature fruits and seeds. In Castanea henryi, an ovary contains 16–24 ovules, but only one develops into a seed. The other ovules abort or otherwise fail to fully develop, but the reason for this is unknown. Such a strict reproductive screening mechanism is rare in plants. Methods In this study, controlled pollination scheme were adopted, and conventional paraffin embedding and semi-thin sectioning techniques, followed by microscopy, were used for cytological studies of ovule development in C. henryi. Results Pollination affected not only the process of ovule development, but also the proportion of ovules that formed mature embryo sacs. Approximately 53.53% of the ovules in the pollinated treatment developed normally, while only 16.55% of the ovules in the unpollinated treatment developed into mature embryo sacs with a seven-cell, eight-nucleated structure. Failure to form mature embryo sacs and the abnormal divisions of the zygote, respectively, were the reasons for the pre- and post-fertilization ovule failures. Our findings not only provide basic information on the reproductive biology and also information on seed production of C. henryi.